The crystal structure of methyl 4-(4-(methylsulfonyl)phenyl)-2-methyl-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylate, C19H21NO5S - Li Yaoyao; Su Lai; Wang Tianqin; Zhang Le (Zeitschrift für Kristallographie - New Crystal Structures)
C19H21NO5S, triclinic, P1̄ (no. 2), a = 8.428(2) Å, b = 10.638(3) Å, c = 11.177(3) Å, α = 63.125(4)∘, β = 77.819(4)∘, γ = 79.845(4)∘, V = 869.9(4) Å3, Z = 2, R gt (F) = 0.0472, wR ref (F 2 ) = 0.1379, T = 296(2) K.